Personality and insomnia: a systematic review and narrative synthesis - Akram, U; Jodie, S; Maria, G; Sarah, A; Anna, J (Wiley, 2023)
The inherent nature of personality serves as a predisposing, and possible maintaining, factor of insomnia. However, methodological differences limit the ability to draw causal conclusions regarding the specific traits involved in the aetiology of the disor- der. This systematic review of the relationship between insomnia and personality provides a narrative synthesis of the literature to date. Here, we identified N = 76 studies meeting the inclusion/exclusion criteria. The outcomes reliably evidenced the experience of insomnia to be associated with personality traits that are typically con- sidered to be negative or maladaptive in nature. More specifically, insomnia was related to neuroticism, introversion, perfectionistic doubts and concerns, elevated personal standards, negative affect, social inhibition and avoidance, hysteria, hypo- chondriasis, psychasthenia, impulsive behaviour, anger, hostility, and psychopathic tendencies, schizotypal and borderline traits, reduced conscientiousness and self- directedness, and negatively perceived perception of the self. Several studies examined the role that personality plays in predicting the treatment efficacy and adherence of CBTi. Moving forward, longitudinal research, methodological consis- tency, the mediating role of treatment outcomes and adherence, and clinical and population representative samples should be prioritised. Methodological strengths and limitations of the literature are discussed alongside the next steps that should be taken to advance our understanding of the literature.